Thermal history of the Northwestern Argentina, Central Andean Basin, based on first-ever reported graptolite reflectance data - Herrera Sánchez, Nexxys Carolina (2021)
The thermal maturity from the Early Paleozoic strata in Northwestern Argentina was studied using reflected light microscopy and Rock-Eval analyses. The graptolites were collected from the Acoite and Lipeón formations, at the Los Colorados section, Cordillera Oriental, and the Huaytiquina, and Muñayoc sections, Puna highland, corresponding to the “Coquena” Formation and the Cochinoca-Escaya Magmatic-Sedimentary Complex. Rock-Eval parameters were unreliable due to the low TOC, S1, and S2 values. The Cordillera Oriental region sediments have low maturity based on low reflectance (%GRo= 0.63%–1.11%) and anisotropy of graptolites. In contrast, the higher graptolite reflectance of samples from the Muñayoc and Huaytiquina sections (%GRo= 5.57%–6.62%), in the Puna region, indicates considerably higher maturity. This could result from the combination of hydrothermal fluids with a temperature range from 336 °C to 358 °C, associated volcanism, and deformation related to tectonics events, which produced a higher geothermal gradient in the Puna. The Los Colorados section's thermal maturity modeling shows a better fit considering erosion episodes at the Late Paleozoic and Early Cenozoic. However, more studies about geothermal parameters and stratigraphy are necessary to corroborate these preliminary models and propose new approaches for the Puna region.